Analisis Self Care Management Terhadap Lansia Pasca Stroke dalam Peningkatan Activities of Daily Living (ADLs): A Systematic Review - Helatul Mardiah; Vivin Nur Hafifah; Zainal Munir; Handono Fatkhur Rahman (FORIKES, 2021)
Elderly with stroke tend to have changes in terms of social life. The purpose of this systematic review is to determine the self-care management of the elderly with post-stroke which has an impact on increasing Activities of Daily Living (ADLs). The source database were Google Scholar, Cambridge core, PubMed, and Proquest, with keywords namely self care management in the elderly after stroke. The period of the articles was 2016-2020, with full text in English or Indonesian, so that we get 15 articles. Self care management provided by cadres or families is very important for the elderly with post-stroke to increase knowledge and motivation to be more independent and able to carry out daily activities without assistance. Keywords: self-care management; elderly people; stroke; Activities of Daily Living (ADLs) ABSTRAK Lansia dengan stroke cenderung memiliki perubahan dalam segi kehidupan sosial. Tujuan systematic review ini adalah mengetahui manajemen perawatan diri lansia dengan pasca-stroke yang memiliki dampak pada peningkatan Activities of Daily Living (ADLs). Database sumber adalah Google Scholar, Cambridge core, PubMed, dan Proquest, dengan kata kunci yaitu self care management in the elderly after stroke. Kurun waktu artikel adalah 2016-2020, dengan teks penuh berbahasa Inggris atau bahasa Indonesia, sehingga didapatkan 15 artikel. Self care management yang diberikan oleh kader atau keluarga sangat penting bagi lansia dengan pasca-stroke untuk meningkatkan pengetahuan dan motivasi untuk lebih mandiri dan mampu melakukan aktivitas sehari- hari tanpa bantuan. Kata kunci: self-Care management; lansia; stroke; Activities of Daily Living (ADLs)